THE STATE OF NEUROPEPTIDE-CYTOKINE STATUS IN ISCHEMIC HEART DISEASE - Khusainova Munira Alisherovna, Yarmakhammadov Usmon Kulmuxammatovich, Eshmamatova Fayyoza Boymamatovna, Shamsutdinov Asadbek Shokirovich (Journals Park Publishing, 2023)
The spread of metabolic syndrome (MS) in developed countries, which, according to WHO experts, assumed the nature of a pandemic in the XXI century, contributes to the increase in the incidence of coronary heart disease (CHD). MS is currently considered a kind of cluster of risk factors for atherosclerosis, coronary heart disease and type 2 diabetes mellitus. Since the main diagnostic sign of MS is abdominal type of obesity, it is natural to assume that if it is present, certain clinical and pathogenetic features should be revealed in patients with coronary heart disease. By a well - known analogy with phenotypes Currently, chronic obstructive pulmonary disease can be considered a special phenotype of coronary heart disease against the background of abdominal obesity. A decrease in the production of endorphins is accompanied by an increase in the activity of the sympathetic system, an increase in the production of cortisol by the adrenal glands, stimulation of gluconeogenesis, increased synthesis of triacylglycerols and lipogenesis, which creates conditions for the potentiation of atherogenesis.
Keywords: ischemic disease, atherosclerosis, anxiety, depression, beta-endorphin, cytokines.